Pentecostal Churches and Capitalism in a South African Township: Towards a Communism of the Market? - Thibaut Dubarry (Journal for the Study of Religion)
With reference to two Pentecostal churches in the Kayamandi suburb of Stellenbosch, South Africa, we consider the ways in which capitalism and the Pentecostal spirit interrelate in a contemporary South Africa. We start off by acknowledging that many forms of Pentecostalism now tend to follow the paradigm set by neo-Pentecostalism, and that the same might be true of our two church communities, Revival Fire Ministries, and the Apostolic Faith Mission, even if the latter is more typically regarded as part of the classical Pentecostal movement in South Africa. Then we discuss Pentecostalism and its relationship to the secular domain. We show how Pentecostalism, in contrast to traditional forms of Christianity, is par excellence involved in the immanent/horizontal affairs of believers’ lives. Indeed, the market itself appears to be sacralized, implying a transfer of holiness into the secular domain. We conclude with the idea that we have observed a fourth wave of Pentecostalism, anticipating that the golden age of Gesara/Nesara may be considered as a secular faith, forming a Hegelian synthesis of the two so-called secular religions of the 20th century, capitalism and communism. We have analyzed it as an apocatastasis, meaning restoration to the original or primordial condition.